SALES PERFORMANCE PREDICTED FROM CAREER DEVELOPMENT AND SPIRITUAL CAPITAL THROUGH DISCIPLINE INTERVENING VARIABLES OF MOTORCYCLE RETAIL COMPANY EMPLOYEES - Yusuf Setiawan; Sutisna Sutisna; Ade Manggala Hardianto (Yayasan Education and Social Center, 2022)
This research aims to construct a predictive model of career advancement, spiritual capital's impact on employee work discipline, and the implications of these factors for sales performance. The research method is a survey method, and it involves distributing questionnaires to a total of 150 employees and using the analysis tools provided by structural equation modelling (SEM). Researchers distributed questionnaires based on indicators including career development 7 indicators, spiritual capital 6 indicators, discipline 5 indicators, and sales performance 11 indicators. The research results on the outer model show that all indicators are accurate, and the hypothesis test is recognized as having significant impacts. Career development and spiritual capital towards discipline are at 2.849 and 8.113 > 1.96. In addition, statistical results show that the profession has a positive effect on sales performance. The significance of the intervention shows that career development (2.087) and spiritual capital (3.052) have an indirect impact through discipline on sales performance (2.087). Limitations of the research It is necessary to invade the object of study to produce a more established model. Therefore, although the researchers restricted the survey area to the city of Cilegon, they still conducted the research